Essential readings in sport and exercise psychology (Human Kinetics, 2007)
From the sandlot to the skybox, psychology plays as hard as the players themselves. In this anthology, which could satisfy the pros as well as undergraduate and graduate students, readers can take their pick from 50 classic and leading edge articles that serve recreational athletes as well as the millionaires in uniforms. Although therapists and those who work in such fields as sports medicine or physical therapy will probably get the most from this, even Saturday morning tennis players will get a better understanding of their game with such topics as understanding the history of sports and exercise psychology and its explosive growth, handling individual difference among sports participants, making the best use of sport and exercise environments, enhancing health and well- being, building group processes, facilitating psychological growth and development, understanding professional issues such as ethics and certification and, of course, enhancing performance. ©2007 Book News, Inc., Portland, OR (booknews.com)